Prognostic value of the neutrophil-to-lymphocyte ratio for predicting hospital length of stay in pneumonia patients: A cross-sectional study - Henny Syapitri; Johansen Hutajulu; Amila Amila; Lasma Rina Efrina Sinurat; Janno Sinaga; Ivan Elisabeth Purba (Nursing and Health Sciences Journal (NHSJ), 2026)
Pneumonia remains a leading cause of hospitalization and mortality globally, imposing a substantial burden on healthcare systems in developing countries. The Neutrophil-Lymphocyte Ratio (NLR) has emerged as a readily accessible, cost-effective prognostic biomarker for predicting hospital length of stay (LOS). This study aimed to examine the association between NLR and LOS in patients with pneumonia at Melati Perbaungan General Hospital. A cross-sectional study was conducted using medical records of patients with pneumonia treated between January 2024 and January 2025. Of the 240 patients, 102 met the inclusion criteria. Exclusion criteria encompassed immunocompromised conditions, chronic comorbidities, surgical complications, and incomplete records. Data collected included neutrophil and lymphocyte counts, NLR, LOS, age, sex, and treatment modalities. Univariate and bivariate analyses were performed using the Chi-square test (p < 0.05). Most patients exhibited elevated neutrophil levels (64.7%) and lymphopenia (47.1%). High NLR (>3.13) was observed in 80.4% of patients. The majority (77.5%) experienced hospital stays exceeding four days. Significant associations were identified between neutrophil levels (p = 0.038), lymphocyte levels (p = 0.044), and NLR (p = 0.031) with LOS. Patients with elevated NLR demonstrated significantly higher odds of prolonged hospitalization (OR = 5.14). NLR is significantly associated with prolonged hospitalization among patients with pneumonia. This readily accessible biomarker may serve as a cost-effective prognostic indicator to support early risk stratification, optimize resource allocation, and improve patient management outcomes in clinical practice.